Investigating the basis of legitimation of English literary studies: a case study of a curriculum at a South African University - Knoetze, Retha (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning)
This study explored the kinds of knowledge, ways of knowing and ways of being that are valued in English literary studies. It did so by providing an analysis of what was needed to succeed in a specific English literary studies curriculum. The study used the Specialisation dimension of Legitimation Code Theory (LCT) to investigate what is legitimated in an English literature curriculum at the University of South Africa (UNISA) across three years of undergraduate study. The purpose of this analysis was twofold. Firstly, it aimed to make the academic literacy practices of English literary studies more explicit in order to inform pedagogy intended to enable epistemological and ontological access to the discipline. Secondly, the study aimed to facilitate critiques of the curriculum from a social justice perspective by finding ways to make the basis for legitimacy (the ways of being and knowing that are valued) in the curriculum more explicit to both the academics and the students. The study found that English literary studies, as practised at UNISA, was underpinned by what LCT refers to as a 'cultivated gaze'. This aligns with the findings of previous LCT studies that looked at English literary studies using the dimension of Specialisation. A discipline that is underpinned by a cultivated gaze requires students to exhibit a specific disposition that develops through immersion in the field over an extended period in order to be considered a legitimate knower. The study also found that two orientations within the cultivated gaze were legitimated in the curriculum: an aesthetic orientation and a socio-critical orientation. This finding adds to the previous research because it helps us to better understand the kinds of dispositions that are valued in English literary studies and how these dispositions are cultivated over time. In addition, the study found that neoliberal factors such as massification, managerialism and academic casualisation caused misalignments between the intended curriculum and the practices employed to teach and assess the curriculum. This placed particular limitations on one of the aims of the curriculum which was to cultivate a socially oriented criticality. This finding has implications for how we teach Humanities curricula that aim to develop critical citizens.
Keywords: Knowledge, Theory of; Critical thinking; English literature-- Study and teaching (Higher) -- South Africa; Neoliberalism -- South Africa; Critical literacy; Transformative learning